The mega distributed lag model - Mario Arturo Ruiz Estrada; Evangelos Koutronas; Ross Knippenberg (Contemporary Economics, 2016)
This paper attempts to describe the graphical behavior of the distributed lag model in an infinite coordinate space. The "mega distributed lag model" (MDL) is a mathematical framework that can examine the simultaneous interrelationships between all involved variables. The multidimensional graphical setting simultaneously reveals all non-linear exposure-response dependencies and delayed effects between lagged and dependent variables-which two-dimensional figures overwhelmingly fail to capture. Under the Omnia Mobilis assumption, each distribution lag function is indexed with respect to time and space. The Mega distributed lag model observes multiple trends in full motion, the final output (determinant) of which is called "the JIM-coefficient". Hence, this paper tries to analyze different approaches of lag distribution models that can help in the construction of our new model. The mega distributed lag model" (MDL) is moving from the uses of the classic 2-dimensional and 3-dimensional graphical modeling to a multidimensional graphical modeling in Econometrics. Finally, this model is an extension of those explored earlier in the field of econographicology.
Keywords: C10; 330; Econographicology; Distributed lag model; Multi-Dimensional graphs; Multi-Dimensional geometry